Simulation and Optimization of One Live Pig Low-Carbon Industry Chain Using SD-RCCM - Jiuping Xu; Jie Yan; Liming Yao (Abstract and Applied Analysis)
The destruction of the natural environment has been drawing more and more attention. Developing low-carbon industry chains is an effective solution to the conflict between rapid economic growth and high CO2 emissions. Summarizing various traditional and new industry chain sustainable development, live pig industry was chosen as a typical industry chain to study low-carbon development using a system dynamics and random chance-constrained model (SD-RCCM). Leshan, a world natural and cultural heritage area in China, was selected as a typical city to analyze the low-carbon pig industry. Three different programs based on distribution ratios were selected to study this industry. The results showed that program 1, which considers both environmental and economic benefits, realizes sustainable development. In order to extend the pig industry chain and fully utilize pig ordure and other waste, introducing a Clean Development Mechanism (CDM) and household biogas exploitation program is recommended.